(untitled) (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
The multi-chain future is already here – Ethereum, Solana, Cosmos, Polkadot, Avalanche, and a growing constellation of L2 rollups each host significant DeFi activity, user bases, and developer communities. But building a cross-chain application today means integrating 3-5 different SDKs, managing separate wallet connections per chain, handling incompatible transaction formats, and navigating a patchwork of bridging solutions with wildly different security assumptions. Cross-chain development frameworks promise to abstract this complexity behind unified APIs, letting developers write once and deploy across chains. We present the Cross-Chain Framework Assessment (CCFA), evaluating five interoperability frameworks – Cosmos IBC SDK, Polkadot XCM/Substrate, LayerZero, Axelar, and Wormhole – across four cross-chain application patterns: asset transfers, cross-chain messaging, multi-chain governance, and unified liquidity. We introduce the Framework Interoperability Score (FIS) measuring chain coverage, developer experience, message reliability, security model strength, and latency. IBC SDK achieves the highest FIS (0.912) within the Cosmos ecosystem but is limited to IBC-compatible chains. LayerZero achieves the highest cross-ecosystem coverage (0.920) with FIS 0.876, making it the practical choice for applications targeting heterogeneous chain environments.